Photocatalytic degradation of polystyrene nanoplastics in water. A methodological study. Issue 4 (August 2022) - García-Muñoz, Patricia; Allé, Paul Henri; Bertoloni, Calogera; Torres, Alvaro; de la Orden, María Ulagares; Urreaga, Joaquín Martínez; Dziurla, Marie-Antoinette; Fresno, Fernando; Robert, Didier; Keller, Nicolas
Abstract: The ability of a wide span of characterization and analytical tools to provide reliable, quantitative data for monitoring the efficiency of photocatalysis in the mineralization of calibrated polystyrene nanobeads was studied. Both slurry and immobilized reaction modes were compared, and polystyrene nanoparticles of different characteristic sizes were used as model compounds for developing a suited methodological approach. We demonstrated that tests in the immobilized mode showed an unequivocal advantage over the slurry mode and in consequence should be preferred to get rid of the restrictive presence of the nanoparticulate photocatalyst within the samples to be analysed. At best, the results in the slurry mode revealed the existence of a photocatalytic activity towards polystyrene nanobeads, with no capacity of reliable quantification. Direct imaging or indirect light-scattering characterization giving a direct access to the size of the nanoplastic particles cannot provide fully relevant data, as the polystyrene substrate was reported to lose its nanobead morphology during the photocatalytic attack, in parts or entirely, with the simultaneous release to the water of polystyrene macromolecules. Py-GC/MS allowed the polystyrene concentration to be followed with time, but with no access to the concentration of polystyrene nanoparticles. TOC analysis remained the most suited and reliable technique to monitor and quantify the mineralization of polystyrene nanoplastics by photocatalysis. UV-Vis spectrophotometry was reported to be a fast, non-destructive alternative technique to TOC analysis in the specific case of polystyrene. Graphical Abstract: ga1 Highlights: The photocatalytic degradation of calibrated polystyrene nanobeads was studied in water Testing in the immobilized mode is more suited than in the slurry mode for quantification Qualitative and quantitative methods were applied for assessing the photocatalytic degradation of nanoplastics TOC analysis is the most reliable tool to quantify the photocatalytic efficiency The nanoplastic size is not a relevant indicator of the photocatalytic degradation